Successful consecutive pregnancies following two uterine artery embolization procedures for symptomatic fibroids - Stojnev, Dzordze; Yordanov, Angel (Menopause Review/Przegląd Menopauzalny, 2025)
Uterine artery embolization (UAE) is a minimally invasive method that has been proven to be an effective alternative to hysterectomy and myomectomy for the treatment of symptomatic fibroids, though its impact on fertility and obstetric outcomes remains controversial. This case report presents a 31-year-old nulliparous woman with a history of fibroid-enlarged uterus (about the size of a 16–20-week pregnancy), who underwent UAE treatment, became pregnant, and delivered a healthy child by cesarean section. At the age of 35, a second UAE was performed due to recurrence of symptoms, followed by a successful conception and delivery of a second child. This report explores the clinical course, management strategies and the role of a multidisciplinary approach in achieving successful outcomes. Although substantial evidence has accumulated in the literature about the safety and effectiveness of UAE as a non-surgical option for uterine fibroids treatment, this procedure still raises questions about its impact on future fertility and obstetric outcomes, including the risk of miscarriage, placenta previa, and preterm delivery. Uterine artery embolization is a promising minimally invasive alternative to myomectomy for women with fibroids who want to preserve their fertility. The present case demonstrates that successful conception and childbirth are possible when patients undergo close follow-up and individualized management.